(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the era of 21st century and highly competitive business environment, the world has become a truly global. And the professionals in the service sector are increasingly under pressure to demonstrate their services as customer- focused and that continuous performance improvements are being delivered. As far as India is concerned, a number of technological and management institutions have been established which have made a significant contribution in producing a large reservoir of technically trained manpower. India can claim the third largest reservoir of scientific and technical manpower in the world. But it is important that along with the quantity of manpower, the emphasis must be on the quality of management education. Therefore, evaluation of the quality of education services of prevailing management education system in India is of utmost significant and efforts need to be made to nurture obsession for quality in institution offering management education. Thus, it is important to analyze and critically review the services on regular basis to identify and correct gaps between desired levels and actual levels of performances. The study has been undertaken to demonstrate the gaps for measuring students’ perception-expectation regarding management education services in Haryana, India which is investigated with the research instrument SERVQUAL Model.